Różnice w korzystaniu ze strategii uczenia się języka angielskiego przez studentów: wnioski z badania - Przybył, Jakub; Małowska, Malwina; Chmielewska, Klaudia; Gawek, Marta; Grzymała, Małgorzata (Neofilolog, 2017)
The present paper investigates the relationships between language learning strategies and their determinants, such as learners’ gender, their area of studies, and personality traits. It describes a study conducted on a group of 199 students of the Faculty of Social Sciences at Adam Mickiewicz University in Poznań. The results of the study indicate that a number of statistically significant relationships exist between strategy use and other individual variables, e.g. gender, level of proficiency, or learners’ area of studies. Moreover, the authors of the study make an attempt to identify and characterise students’ profiles in terms of their personal characteristics and strategic preferences so as to cast light on various paths to foreign language proficiency.